Angiotensin-Converting Enzyme Inhibition and Parathyroid Hormone Secretion. (20th July 2017) - Zaheer, Sarah; Brown, Jenifer M.; Connors, Molly; Williams, Jonathan S.; Adler, Gail K.; Vaidya, Anand
Abstract : Background . Prior studies suggest that renin-angiotensin-aldosterone system (RAAS) inhibitors decrease parathyroid hormone (PTH) secretion. Objective . To evaluate the effect of angiotensin-converting enzyme inhibitors (ACEi) on serum PTH in participants with and without primary hyperparathyroidism (P-HPT). Methods . An open-label, single-arm, pilot study whereby participants with and without P-HPT had PTH were evaluated before and after 1 week of maximally tolerated lisinopril therapy. Results . A total of 12 participants with, and 15 participants without, P-HPT successfully completed the protocol. Following 1 week of lisinopril, participants with P-HPT had a decrease in systolic blood pressure (SBP) (−6.4 mmHg, P < 0.01 ), an increase in plasma renin activity (PRA) (+1.50 ng/mL/h, P = 0.06 ), and a decrease in PTH (79.5 (21.6) to 70.9 (19.6) pg/mL, ∆ = − 8.6 pg/mL, P = 0.049 ); however, serum and urine calcium did not change. In contrast, although 1 week of lisinopril significantly decreased SBP and increased PRA among participants without P-HPT, there were no changes in PTH or calcium. Conclusion . In this short pilot investigation, 1 week of maximally titrated ACEi did not impact PTH in participants without P-HPT, but resulted in a modest and marginally significant reduction of PTH but not calcium, among participants with P-HPT. This trial is registered with ClinicalTrials.gov NCT01691781 .